2020
DOI: 10.5797/jnet.cr.2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with a Ruptured Blood Blister-like Aneurysm of the Internal Carotid Artery in Whom Two LVIS Stents Were Inserted

Abstract: We report a case in which multiple overlapping low-profile visualized intraluminal support (LVIS) stents were used as monotherapy for ruptured blood blister-like aneurysm (BBA) of the internal carotid artery (ICA). Case Presentation: A 48-year-old female presented to the emergency room with acute-onset headache. She was alert without neurological deficit with subarachnoid hemorrhage (SAH) Hunt and Kosnik grade I. Emergency angiography revealed a BBA from the supraclinoid ICA. This aneurysm had a small diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The efficacy of overlapping stents has been reported in case reports or treatment results of single institutions by Suzuki et al 6) and Ji et al 7) Lim and Song 15) treated 16 patients with overlapping stents and 1 with SAC. Three of the patients died, whereas 14 achieved CO during the follow-up DSA.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The efficacy of overlapping stents has been reported in case reports or treatment results of single institutions by Suzuki et al 6) and Ji et al 7) Lim and Song 15) treated 16 patients with overlapping stents and 1 with SAC. Three of the patients died, whereas 14 achieved CO during the follow-up DSA.…”
Section: Discussionmentioning
confidence: 91%
“…Yu et al 5) reported 13 patients with BBA between 2004 and 2010 treated using SAC: 6 had no deficit, 3 had ischemic complications, 3 died from rebleeding, and 1 died from a central nervous system infection. 6) Recent articles have also reported the efficacy and safety of SAC. Roh et al 10) reported, using pooled analysis, that the rates of good outcome were 89.9%, rebleeding was 7.94%, recurrence was 24.2%, and the mortality rate was 7.7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations